A novel seismic-resistant reconstruction technique for fair-face rubblestone masonry - Sangirardi, Marialuigia; De Santis, Stefano; Roselli, Ivan; Liberatore, Domenico; de Felice, Gianmarco (Engineering structures, 2025)
After destructive earthquakes reconstruction is sometimes preferable over repair. In historic centres, this requires a wise balance between safety and compatibility with urban context, where the preservation of the fair face of masonry façades is an invaluable architectural asset. This paper proposes an innovative technology for the reconstruction of fair-face rubblestone masonry, consisting in a two-leaf structure. The internal leaf is made of reinforced hollow-clay masonry, and provides seismic resistance. The external leaf is built in fair-face rubblestone masonry, consistently with the pre-existing façade, possibly using the stones recovered from debris, avoiding their disposal and the supply of new materials. A glass fibre reinforced polymer mesh is laid in the bed joints, connecting the two leaves and preventing the disintegration of rubble masonry. The technique was validated through shake table tests on a full-scale prototype subject to out-of-plane vertical bending under natural seismic inputs. The prototype withstood earthquake motions nearly three times as intense as those recorded during the destructive 2016–2017 Central Italy seismic sequence, the maximum base acceleration being 1.7 g. Apart from limited hairline cracks, no signs of rubblestone disintegration or leaf separation were detected, measured relative displacements were less than 1 mm, and no residual deformations were detected. Design criteria are provided to allow the implementation of the proposed technology in post-earthquake reconstruction. •A technology to reconstruct masonry buildings in earthquake prone areas is proposed.•Walls are made of two connected leaves of reinforced and rubblestone masonry.•A connecting glass fibre reinforced polymer mesh is placed in bed joints.•The seismic performance of the wall is tested on a shake table.•Design criteria accounting for seismic actions are proposed.